“Worn-out but happy”: Postpartum Women's Mental Health and Well-Being During COVID-19 Restrictions in Australia - Christie, Hannah E.; Beetham, Kassia; Stratton, Elizabeth; Francois, Monique E. (Frontiers in Global Women's Health, 2022)
Background: From late 2019, COVID-19 disease has infiltrated the global population causing widespread challenges to public health. One cohort that has received less attention, but who may be more vulnerable to the mental and physical health related impacts of COVID-19 restrictions are postpartum mothers. The aim of this study was to explore the mental health, wellbeing, and health behaviours of mothers up to 12 months postpartum whilst living in Australia under COVID-19 level 3 and 4 restrictions. Methods: 351 women in their first year postpartum residing in Australia whilst under level 3/4 social distancing restrictions (during April 13 and June 11, 2020) were recruited to participate in an online questionnaire. The survey measured symptoms of depression, anxiety, and stress (DASS), wellness (SF-36), physical activity (Godin-Shephard score), perceived value of health outcomes, diet, and sleep. Descriptive statistics and linear regressions were performed. Results: Data were analysed for 139 eligible women. Of these women, 74% scored ‘normal’ for depression, 84% for anxiety, and 72% for stress. Over half (58%) of women reported being worn out all, most, or a good bit of the time and 77% reported being a happy person all, most, or a good bit of the time. Analysis of the perceived values of health outcome revealed women had high value for ‘getting out of the house,’ ‘achieving a better overall mood’ and ‘to feel better physically’. Women were considered physically active according to the Godin Leisure score, however only 41% of women met the current Australian national physical activity guidelines of 150 min.week-1. Conclusions: Overall the majority of postpartum mums that were surveyed, have normal mental health symptoms, and despite being worn out most are happy at least a good bit of the time. This study highlights the importance of health values in maintaining leisure physical activity and mental health. In addition it appears women may benefit from virtual group exercise and community programs to encourage being physically active and socialising with friends simultaneously.